Towards a Syntax-Semantics Interface for Latin - Andrew M. Devine (Universitat Autònoma de Barcelona, 2017)
Latin is often cited as a typical example of a free word order language. Free word order inevitably complicates the compositional semantics for any theory in which functions are lexically defined to take their arguments in a fixed order. A number of sophisticated logical mechanisms have been suggested over the years to resolve this problem, but none of them is actually compatible with the Latin data. We adjust the syntax to fit the philological evidence and use the resulting structure as the basis for a simple semantics which allows arguments to be entered into the semantic composition in the order in which they are presented by the syntax.